The Non-Linear Impact of Medium and High-Technology Manufacturing on Environmental Quality: Evidence from Leading Technological Economies Using a PSTR Approach - Boussaidi, Ramzi; Jebli, Mehdi Ben; Bakoben, Hussam Buzaid M. (International Journal of Energy Economics and Policy, 2025)
High-tech manufacturing presents a dual challenge: while it offers opportunities to enhance environmental quality through innovation and efficiency, it can also exacerbate environmental risks if not properly managed. This study explores the non-linear relationship between medium and high-technology manufacturing (MHTM) and CO2 emissions, utilizing data from 12 leading MHTM countries over the period 1990-2021. Employing the Panel Smooth Transition Regression (PSTR) model of Gonzàlez et al. (2005), the analysis uncovers a threshold effect in the MHTM-CO2 emissions nexus. Specifically, an MHTM threshold of 56.68% is identified: below this level, MHTM significantly increases CO2 emissions, whereas, above it, MHTM significantly reduces emissions, thereby enhancing environmental quality. The findings also reveal a threshold-dependent effect of renewable energy (RE); below the threshold, RE increases CO2 emissions, while above it, RE significantly improves environmental quality. Conversely, non-renewable energy (NRE) and trade consistently contribute to environmental degradation, regardless of the threshold. Sensitivity analyses, based on European and non-European sub-samples, show that for European countries, MHTM reduces emissions both below and above a threshold of 58.49%. For non-European countries, however, significant reductions in CO2 emissions occur only when MHTM exceeds a threshold of 66.7%. These results provide critical insights into the nuanced role of technology, energy, and trade in shaping environmental outcomes.